Havana beyond the ruins : cultural mappings after 1989 - Birkenmaier, Anke; Whitfield, Esther Katheryn (e-Duke books scholarly collection., 2011)
Looks at portrayals of Havana in literature, music, and the visual arts in the post-Soviet era, as the city is reinvented as a destination for international tourists and business ventures.